Mechanısms of Fınance of Small Busıness Enterprıses - Asatullaev Xurshid Sunatullaevich , Ergashev O.T. (International Journal of Advanced Science and Technology, 2020)
The issues of crisis, causes diversification, modernization, gross domestic product, employment, investment, credit, microcredit, investment project, foreign investment, machinery of financing, localization, business plan, financial strategy, private property, business sphere, nonbank credit organization, family business.